Implementasi Sistem Informasi Akuntansi Kredit Gadai Emas Di PT Pegadaian - Meilinda, Yesica; Triandi, Triandi; Kusuma, Rahma Djati; Pramiudi, Udi (Program Vokasi dan LPPM IBI Kesatuan, 2024)
This research was prepared to determine the procedures for granting, repaying, and auctioning gold pawn loans at PT Pegadaian (Persero) Tajur Branch Service Unit as one of the Fast and Secure Credit products offered by the company to the public to be able to obtain loans with collateral in the form of gold. The purpose of this writing is to find out about the Gold Pawn Credit Accounting Information System at PT Pegadaian and how the effectiveness of Internal Control on the Gold Pawn Information System at PT Pegadaian. The procedure for granting a gold pawn starts from a credit application, valuation of collateral, disbursement of credit loan funds, to storage of collateral, followed by settlement of the loan money within a maximum of four months by redemption, installments, or renewal. If the customer is unable to repay later, the collateral will be auctioned with the customer's consent based on the terms and conditions at the beginning of the credit loan process. Based on the results of the review, all of the above procedures have been carried out by the principles of good internal control, including standard procedures that are outlined in the form of flowcharts, there is a separation of duties made in the organizational structure and job descriptions, there are appraisers to overcome the risk of the insufficient value of collateral, there are adequate authorization procedures when granting credit and the auction process, there is verification of credit granting requirements, security of pawn deposits is very adequate, supported by a pawn application system and supporting documents to ensure the achievement of the objectives of granting credit with gold pawning. Keywords: Gold Pawn Credit Procedure, Internal Control, Accounting Information System